An efficient causal ordering algorithm for mobile computing environments - Prakash, R.; Raynal, M.; Singhal, M. (Proceedings of the 16th International Conference on Distributed Computing Systems, 1996)
Causal message ordering is required for several distributed applications. In order to preserve causal ordering, only direct dependency information between messages with respect to the destination process(es) should be sent with each message. By eliminating other kinds of control information from the messages, the communication overheads can be significantly reduced. In this paper we present an algorithm that uses this knowledge to efficiently enforce causal ordering of messages. The proposed algorithm does not require any prior knowledge of the network or communication topology. As computation proceeds, it acquires knowledge of the logical communication topology and is capable of handling dynamically changing multicast communication groups. With regard to communication overheads, the algorithm is optimal for the broadcast communication case. Its energy efficiency and four bandwidth requirement make it suitable for mobile computing systems. We present a strategy that employs the algorithm for causally ordered multicasting of messages in mobile computing environments.